2020
DOI: 10.1002/sctm.19-0392
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the increased intracellular pH of human-induced pluripotent stem cell-derived endothelial cells induces formation of mature Weibel-Palade bodies

Abstract: Differentiation of human-induced pluripotent stem cells (hiPSCs) into vascular endothelium is of great importance to tissue engineering, disease modeling, and use in regenerative medicine. Although differentiation of hiPSCs into endothelial-like cells (hiPSC-derived endothelial cells [hiPSC-ECs]) has been demonstrated before, controversy exists as to what extent these cells faithfully reflect mature endothelium. To address this issue, we investigate hiPSC-ECs maturation by their ability to express von Willebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The existence of regular tubules of ultra-large vWF is an indicator of WPB maturation that is a driving force to form rod-shaped WPBs ( McCormack et al, 2017 ; Tiemeier et al, 2020 ). Studies have shown that vWF is released by regulated secretion and unfurls into long strings that are highly efficient in recruiting platelets under flow in neutral plasma ( Michaux et al, 2006 ; Ferraro et al, 2014 ; El-Mansi and Nightingale, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of regular tubules of ultra-large vWF is an indicator of WPB maturation that is a driving force to form rod-shaped WPBs ( McCormack et al, 2017 ; Tiemeier et al, 2020 ). Studies have shown that vWF is released by regulated secretion and unfurls into long strings that are highly efficient in recruiting platelets under flow in neutral plasma ( Michaux et al, 2006 ; Ferraro et al, 2014 ; El-Mansi and Nightingale, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Parallel to this study, our collaborating group published a paper in which the intracellular pH of hiPSC-ECs was lowered with acetic acid [18]. They showed that, in combination with the (adjusted) Orlova protocol, elongated WPBs appeared in the hiPSC-ECs upon lowering the pH,…”
Section: Ph Lowering Of Culture Environmentmentioning
confidence: 80%
“…Interestingly, our data show that 3PO inhibits the angiogenic sprouting of iPSC-ECs, which suggests that, like HUVECs, they undergo the same metabolic switch to use glycolysis as the main energy source during angiogenic sprouting [ 21 ]. While it has been shown that some endothelial cells differentiated from iPSCs have lower activity of glycolysis [ 27 ], the question remains how the culture conditions dictate the cells phenotype, and whether this effect could be attributed to the specific cues added by our culture platform. For example, it has been shown that both tip cells and non-tip cells use glycolysis as well as mitochondrial respiration for energy production, and that this balance depends on microenvironmental circumstances [ 28 ].…”
Section: Discussionmentioning
confidence: 99%